DINAMIKA KOALISI PKB DAN GERINDRA PADA PEMILIHAN KEPALA DAERAH PROVINSI RIAU TAHUN 2018 - Erla Wepa Afrilia; M. Y. Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Election of regional heads (Pilkada) is carried out directly by the people of the local administrative regions who meet the requirements. Election of regional head and deputy regional head (Pilkada), one element that cannot be left out is the importance of the existence of political parties. Riau Province is one of the provinces that held a democratic party to elect the Governor and Deputy Governor on 27 June 2018. There are four candidate pairs in the 2018 Riau regional head election, one of them is the pair with the second order number, Lukman Edy and Hardianto. This coalition is supported by two parties namely PKB and Gerindra. This coalition was formed at the deadline and a new figure from Gerindra, Hardianto, was chosen to accompany Lukman Edy in the Riau regional elections in 2018. However, the results of the couple's vote was the lowest of the three other pairs. This study aims to determine the dynamics of the formation of the PKB and Gerindra coalition in the Regional Head election in Riau Province in 2018 and to find out the causes of the PKB and Gerindra coalition defeat in the Regional Head election in the Province of Riau in 2018. Furthermore, the data sources used in this study are primary data and secondary data. Data collection methods used in this study were interviews and documentation. The results of this study are the PKB and Gerindra coalition which leads to Arent Lijphart's theory of bargaining proposition because it was formed at the end of time with a small number of coalitions remaining. Hardianto was present because the Gerindra exchange rate was only as Deputy Governor. The defeat of Lukman Edy and Hardianto's coalition included the weak figure of Hardianto, carried by two middle parties while its opponents are carried by several parties, there is no regeneration of PKB figures, less solid political machinery and less mature coalitions, the smallest campaign budget funds. Keywords: Dynamics, Coalition, Political Parties, Riau Regional Head Election